HUMAN RESOURCES MANAGEMENT OF FINANCIAL CONTROLLING OF AGRICULTURAL COMPANIES - O. O. Klokar; I. V. Svynous; O. Y. Gavryk; R. Yu. Ivanova (Фінансово-кредитна діяльність: проблеми теорії та практики, 2019)
Integration of Ukraine into the world economic space, the effective implementation of socio-economic reforms to this effect and an improvement in the standard of living of citizens is not possible without qualitative management of human resources management of financial controlling services, first of all, in agricultural companies. Given the urgency and the unresolved state of problem described above, its insufficient study, the main objective of this research is the characterization of human resources management of financial controlling services in agricultural companies and measures for their effective implementation.